Complete Feed Silage Innovation: Utilization of Agro-Industry by-Products with Chestnut Tannin as Additives - Sadarman, Sadarman; Febrina, Dewi; Febriyanti, Rahmi; Peter, Reski; Zulkarnain, Zulkarnain; Sirajuddin, Sirajuddin; Gazali, Imam; Hafid, Agus; Qomariyah, Novia; Sastrawan, Sandri; Prihambodo, Tri Rachmanto (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study evaluated the effect of chestnut tannin as a silage additive on agro-industrial by-products for animal feed. The research utilized a Completely Randomized Design with five treatments and five replications. The treatments were T1 (Complete Feed as control) and T2, T3, T4, and T5 with chestnut tannins at 0.50%, 1%, 1.50%, and 2% DM, respectively, all fermented for 30 days at room temperature. Observed parameters included proximate analysis (crude protein, crude fat, crude fiber, and ash), temperature, humidity, mold growth, dry matter loss, physical quality of silage (texture, aroma, color), and fresh silage quality. The data were analyzed using variance analysis and DMRT at a 5% significance level. The results showed that the addition of 2% chestnut tannin can produce silage with relatively higher crude protein, while oil fat and crude fiber are relatively the same as other treatments; however, the addition of 2% chestnut tannin tends to produce silage with ash content relatively lower than other treatments. Chestnut tannins significantly affected (P<0.05) moisture, texture, aroma, ammonia, and total VFA of fresh silage. In conclusion, adding 1.50-2% chestnut tannins to complete feed silage reduces dry matter loss, protects crude protein, maintains physical quality, inhibits mold growth, and stabilizes temperature, resulting in high-quality silage.